INDIGENOUS VOLATILE OILS AS IMPERATIVE GIFT FROM NATURE - A REVIEW - Thakur, Raneev; Bhart, Chhveen; Panwar, Kartik; Arya, *Vikrant (International Journal of Ayurveda and Pharma Research, 2018)
Volatile oils are concentrated odorous essences extracted from various plant parts such as flowers, fruits, heart-wood, rhizome and leaves. They are frequently employed in food flavoring, perfume, medicine and aromatherapy. Essential oils are extracted from various processes such as hydro distillation, effleurage and eucelle depending upon the plant part containing the essential oil. Essential oils are inhaled in the form of fine mist of vapour through aromatherapy and some of them are highly beneficial when ingested. These oils have been used traditionally for preservation of foods, spices and condiments. Essential oils or ethereal oils are natural, complex, multi-component, highly concentrated essences of aromatic plant systems composed mainly of terpenes units in addition to some other non-terpene components. These units biosynthesized by mevalonic acid pathway. Isoprenes/hemi-terpenes are five carbon compound having two unsaturated bonds. In this review paper an attempt has been done to emphasize the most valuable essential oils of Indian origin from nature with focus particularly on the chemical constituents, medicinal and pharmacological usage of volatile oils.